(untitled) (Tạp chí Y học Cộng đồng, 2026)
Background: Patient waiting time is a critical indicator of healthcare service quality that significantly influences patient satisfaction and healthcare outcomes. In Vietnam, extended waiting times remain a persistent challenge despite national regulatory frameworks established by the Ministry of Health. This study addresses a critical gap in understanding patient flow dynamics within provincial hospitals, contributing essential evidence to Vietnam’s ongoing healthcare reform efforts aimed at service decentralization and quality improvement. Objective: This study aimed to assess patient waiting times at Kien An Hospital, identify factors influencing these durations, and develop evidence-based recommendations for service improvement that align with Vietnam’s national healthcare transformation agenda. Methods: A mixed-methods approach combining quantitative and qualitative methodologies was employed. Quantitative data were collected from 250 outpatients through structured observation and questionnaires. Qualitative data was gathered through in-depth interviews with 15 participants. Analysis included descriptive statistics, comparative analysis, and thematic content analysis. Results: Patients experienced a mean waiting time of 172.05 ± 6.90 minutes, with diagnostic testing consuming the largest proportion (80.44 ± 4.25 minutes). Morning consultations required significantly longer waiting times than afternoon appointments (190.10 ± 8.03 versus 101.60 ± 6.47 minutes, p<0.001). No significant differences were observed between insured and uninsured patients. Qualitative analysis identified primary contributing factors including specialist workforce shortages, procedural inefficiencies, inadequate separation of outpatient and inpatient diagnostic services, and information technology limitations. Conclusion: The multifaceted nature of waiting time determinants at Kien An Hospital necessitates a comprehensive implementation approach. This research provides actionable insights that hospital administrators and policymakers can use to enhance patient-centered care delivery and optimize resource allocation, directly supporting Vietnam’s strategic healthcare priorities of improving accessibility, efficiency, and service quality at the provincial level.